Prognostic significance of neutrophil count on in-hospital mortality in patients with acute type A aortic dissection - Feng, Weiqi; Li, Huili; Wang, Qiuji; Li, Chenxi; Wu, Jinlin; Yang, Jue; Fan, Ruixin (Frontiers in Cardiovascular Medicine, 2023)
Backgrounds The goal of this study was to assess the impact of neutrophil count, in patients with acute type A aortic dissection (ATAAD). Methods This study retrospectively collected data from patients between September 2017 and June 2021. Youden's index was used to determine the optimal cut-off value for the neutrophil count and patients were divided into two subgroups. A restricted cubic spline (RCS) was used to model the relationship between variables and in-hospital mortality. The least absolute shrinkage and selection operator (LASSO) method and multivariate logistic regression analyses were used to investigate the independent prognostic factors for in-hospital mortality in patients with ATAAD. Results A total of 467 patients were enrolled in this study. In-hospital mortality was 7.28%. The group with elevated neutrophil counts had significantly higher mortality than the group with decreased neutrophil counts (10.8% vs. 3.2%, P = 0.02). This data shows that elevated neutrophil count was significantly associated with in-hospital mortality (OR 3.07, 95% CI 1.22–7.62, P = 0.02). Conclusions Neutrophil count is an independent risk factor for in-hospital mortality in patients with ATAAD. It is an effective inflammatory index, which can be individualized for patients.